Effect of Cold Plasma Treatment on Total Dissolved Solids (TDS) Concentration and Functional Groups in Turmeric (Curcuma longa) Powder in Water - shoodiqin, dian mart; Robiandi, Fadli; Ginting, Jesika Br; Fadilla, Angelika Putri (JST (Jurnal Sains Terapan), 2025)
Cold plasma technology has garnered increasing interest in food and agricultural applications due to its ability to induce surface modifications in organic materials without the use of high temperatures. While its antimicrobial properties are well-documented, recent studies have highlighted its potential in altering the physicochemical characteristics of biopolymers, particularly through modification of surface functional groups. These modifications can influence material behavior in aqueous environments, including solubility and dispersion properties. Turmeric (Curcuma longa), widely used for its bioactive compounds, often faces limitations in its application due to poor solubility in water. Enhancing its solubility could increase its bioavailability and broaden its use in food and pharmaceutical products. This study investigates the effect of cold plasma treatment on turmeric powder, particularly its impact on the concentration of total dissolved solids (TDS) and the modification of functional groups that contribute to solubility. By exposing dried turmeric powder to cold plasma, this work aims to assess its potential to improve the aqueous dissolution of turmeric through structural and chemical surface changes, as characterized by Fourier-transform infrared spectroscopy (FTIR). The results indicate an increase in polar groups such as O–H, N–H, and C–O, and a reduction in non-polar groups such as aliphatic C–H. These modifications suggest enhanced hydrophilicity and solubility of the plasma-treated turmeric powder compared to the untreated sample. Overall, this study demonstrates that cold plasma treatment can serve as an effective technique to improve the solubility characteristics of turmeric, potentially expanding its applications in food, and pharmaceutical